Hypertonic saline resuscitation protects against kidney injury induced by severe burns in rats - Yuan, Chun-Yu; Wang, Qin-Cheng; Chen, Xu-Lin; Wang, Qiang; Sun, Cong-Song; Sun, Ye-Xiang; Wang, Chun-Hua; Su, Ming-Xing; Wang, Hai-Ying; Wu, Xue-Sheng (Burns, 2019)
Proper fluid resuscitation can relieve visceral damage and improve survival in severely burned patients. This study compared the effectiveness of resuscitation with 400mEq/L hypertonic saline (HS) and sodium lactate Ringer’s solution (LR) in rats with kidney injury caused by burn trauma. Rats (Sprague-Dawley) underwent burn injury and were randomized into sham, LR, and HS groups. Samples from the kidney were assayed for water content ratio, histopathology, and oxidative stress (superoxide dismutase (SOD) and malondialdehyde (MDA)). Serum sodium, renal function (creatinine and cystatin (Cys)-C), and inflammatory response (tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and high mobility group protein box (HMGB)-1) were also examined as serum markers. Hypertonic saline resuscitation reduced the renal water content ratio and improved renal histopathology caused by severe burns. This effect was accompanied by reductions in serum creatinine and Cys-C as well as TNF-α, IL-1β, and HMGB1. Serum sodium concentration and SOD activity were increased, whereas MDA content was decreased in the kidney tissue of the HS group. The data indicate that 400mEq/L HS solution reduces hyponatremia and renal edema, inhibits the release of inflammatory mediators, and alleviates oxidative stress injury, thus protecting against kidney injury induced by severe burns.